Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 5 - Exponents and Polynomials - Chapter 5 Test - Page 232: 22



Work Step by Step

[$(x^{-3})(y^{5})]^{-2}$ = Remove square brackets. $(x^{-3})^{-2}$ $\times$ $(y^{5})^{-2}$ = Simplify. $x^{6}$ $\times$ $y^{-10}$ = Recall the following rule: $(\frac{a}{b})^{-x}$ = $\frac{b^{x}}{a^{x}}$. Thus, we obtain: $x^{6}$ $\times$ $\frac{1^{10}}{y^{10}}$ = $x^{6}$ $\times$ $\frac{1}{y^{10}}$ = $\frac{x^{6}}{y^{10}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.